OPEC+ OIL COOPERATION IN THE STABILITY OF GLOBAL OIL - Abbas Ali Jumaah; Dr. Hussein Shanawa Majeed (Scholar Express Journals, 2023)
Oil markets are one of the most important markets because they are dealt with the most important source of energy, namely crude oil, and this market is driven by the law of supply and demand in addition to the economic and political factors that govern it, among these factors we study relative prices, the rate of economic growth, climate change, oil reserves and other important factors, this study relied on the descriptive and analytical method using tables and data available from their official sources on oil prices and their rise and decline according to years, the research aims to highlight On the importance and role of OPEC with other oil-producing countries or the so-called OPEC agreement in regulating oil supply and maintaining production quotas in order to achieve balanced prices, in order to control the prices of the oil market in accordance with market requirements and in accordance with the theory of supply and demand, this study concluded that the entry into force of the OPEC+ agreement and decisions to reduce production helped the oil market a lot to get out of the price crisis due to the Cornea epidemic
Keywords: OPEC; Agreement; Challenges Facing OPEC; Global Oil Market